Confirmatory Factor Analysis to Measure the Satisfaction Level of Air Soda Tourists in North Tapanuli - Nia Shantian Lumbantobing; Susiana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Soda Water Tourism Object (WAS) in North Tapanuli is a bathing tourism area that has the potential to continue to develop. In the development of a tourist spot it is necessary to pay attention to the level of tourist satisfaction. The purpose of this study was to determine the level of satisfaction and the factors that influence the level of satisfaction in WAS. The method used to measure it is Confirmatory Factor Analysis (CFA) to test whether the model built has a relationship with the factors formed. The results showed that the level of satisfaction of WAS tourists was 69.132% or at the level of quite satisfied and the factors that influence the level of satisfaction were service factors, image of tourist attractions, clear information, responsiveness, comfort, facilities, problem and cost handling, natural resources and unique tourist spots.